Preparation of NiO-CuO-MgO fine powders by ultrasonic spray pyrolysis for carbon nanofibers synthesis; Chemical Physics Letters; Vol. 684 - Krasnikova I. V. Irina V.; Mishakov I. V. Iljya Vladimirovich; Bauman Y. I. Yury I.; Karnaukhov T. M. Timofey Mikhaylovich; Vedyagin A. A. Aleksey Anatolievich (2017, 2017)
Title screen